Pendampingan pembibitan generatif dan penggunaan Trichoderma Spp. kepada petani Kopi Di Distrik Minyambouw: Generative Breeding Assistance and The Use of Trichoderma spp. to Coffee Farmers in Minyambouw District - Reymas Ruimassa; Antonius Suparno; Linda Lindongi; Saraswati Prabawardhani; Veronica Tuhumena; Illona Noya; H.J. Namserna; Fenny Asyerem; Budiyono Budiyono; Syukur Karamang; Theresia Tan; Yohanis Mustamu; Amelia Sarungallo; Purbokurniawan Purbokurniawan; Imam Widodo; Yacob Bodang; Adelin Tanati; Baso Daeng; Ina Rumainum; Liz Andriyani (Fakultas Peternakan Universitas Papua, 2023)
Coffee plant (Coffea arabica) is a superior plant to be developed in the Arfak mountain region due to suitable agro-climatic conditions. The way to develop it can be done in various ways, one of which is to develop it independently using seeds from farmers' gardens. This goal can be achieved if the local farming community is able to prepare seeds that HAVE high growth potential and are healthy, free from pests and diseases, especially diseases that are transmitted through the soil (seed born pathogens). The method used includes first, mentoring and discussion at the Kwau Village Hall which includes lectures and discussions about generative nurseries and the use of Trichoderma spp to treat soil borne diseases. The second method is a demonstration of how to plant cocoa seedlings in the farmer's garden accompanied by the application of Trichoderma spp. Both methods were successfully implemented and the community showed high enthusiasm as seen from the questions asked. In this mentoring activity, 60 coffee seedlings were distributed to be developed by coffee farmers. Keywords: Arabica coffee; Kwau; Trichoderma spp.